Using Digital Concept Maps in Conflict Resolution Studies: Implications for Students’ Argumentative Skills, Domain-Specific Knowledge, and Academic Efficacy - Kapshuk, Yoav; Alt, Dorit (Frontiers in Psychology, 2022)
While argumentation emerges as one of the major learning skills in the 21st century, a somewhat opaque landscape is revealed in terms of identifying its potential in enhancing higher-education students’ domain-specific knowledge. In this study, argumentation-for-learning activity with digital concept mapping (CM) was designed and compared with a traditional teacher-centered activity to determine the former's effectiveness in promoting students’ domain-specific factual, conceptual, and procedural knowledge. This study also examines how the proposed activity may contribute to students’ academic efficacy and thus promote meaningful learning. A quasi-experimental design was employed by using convenience samples. Two identical courses were selected for this research: the first course with a total of 59 students (the research group), and the second course including a total of 63 students (the control group). Both groups’ domain-specific knowledge was assessed before and after the activity. The designed activity was found to be less effective in fostering factual knowledge and more effective in developing the conceptual and procedural knowledge domains. Another finding demonstrated the benefits of argumentation for learning with CM in facilitating students’ academic efficacy. It can be concluded that engaging students in a deep argumentation learning process may in turn deepen predominantly conceptual and procedural domain-specific knowledge. Limitations and implications are discussed.